Peptide antagonists of the calcitonin gene‐related peptide (CGRP) receptor with improved pharmacokinetics and pharmacodynamics. Issue 4 (19th July 2013) - Miranda, Les P.; Shi, Licheng; Holder, Jerry R.; Wright, Marie; Gegg, Colin V.; Johnson, Eileen; Wild, Kenneth; Stenkilsson, Michael; Doellgast, George; Manning, Barton H.; Salyers, Kevin
ABSTRACT Antagonism of the calcitonin gene‐related peptide (CGRP) receptor may be a useful approach for migraine treatment. Selective PEGylated peptide antagonists to the CGRP receptor are described, derived from CGRP(8–37) with polymer derivatization at an engineered lysine‐25 residue. Potent PEGylated peptides with improved pharmacokinetics were identified through peptide side‐chain modification to mitigate metabolic liabilities. PEGylated Ac‐Trp‐[Cit11, 18, hArg24, Lys25, Asp31, Pro34, 1‐Nal35]CGRP(8–37)‐NH2, 9, elicits a dose‐dependent reduction of intradermal CGRP‐induced local blood flow in rodents with an ED50 of 0.52 mg kg−1 without any overt adverse effects. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 422–430, 2013.